Śmierć komórek zwojowych siatkówki w przebiegu jaskry – patomechanizm i potencjalne możliwości leczenia. Część II. - Rokicki, Wojciech; Dorecka, Mariola; Romaniuk, Wanda (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Glaucoma is a kind of optic neuropathy where selective retinal ganglion cell loss is the major hallmark. Frequently glaucoma is associated with elevated intraocular pressure, but this condition is neither necessary nor sufficient for onset and progression of the disease. The exact mechanism(s) of ganglion cell death in glaucoma and fully effective treatment of glaucomatous neuropathy still remain unknown. This article reviews the recent researches relevant to IOP–independent risk factors, mechanisms of RGC death and modern potential therapeutic strategies in glaucoma. Part two includes review of ionic derangements, reactive oxygen species cytotoxicity, role of nitric oxide and immunity disorder findings in glaucoma.